On the future : prospects for humanity - Rees, Martin J., 1942- (Princeton, New Jersey : Princeton University Press, 2018)
"Humanity has reached a critical moment. Our world is unsettled and rapidly changing, and we face existential risks over the next century. Various outcomes--good and bad--are possible. Yet our approach to the future is characterized by short-term thinking, polarizing debates, alarmist rhetoric, and pessimism. In this short, exhilarating book, renowned scientist and bestselling author Martin Rees argues that humanity's prospects depend on our taking a very different approach to planning for tomorrow. The future of humanity is bound to the future of science and hinges on how successfully we harness technological advances to address our challenges. If we are to use science to solve our problems while avoiding its dystopian risks, we must think rationally, globally, collectively, and optimistically about the long term. Advances in biotechnology, cybertechnology, robotics, and artificial intelligence--if pursued and applied wisely--could empower us to boost the developing and developed world and overcome the threats humanity faces on Earth, from climate change to nuclear war. At the same time, further advances in space science will allow humans to explore the solar system and beyond with robots and AI. But there is no "Plan B" for Earth--no viable alternative within reach if we do not care for our home planet. Rich with fascinating insights into cutting-edge science and technology, this accessible book will captivate anyone who wants to understand the critical issues that will define the future of humanity on Earth and beyond."--
Our world is unsettled and rapidly changing, and we face existential risks over the next century. Various outcomes are possible, yet our approach to the future is characterized by short-term thinking, polarizing debates, alarmist rhetoric, and pessimism. Rees argues that the future of humanity is bound to the future of science and hinges on how successfully we harness technological advances to address our challenges. -- adapted from publisher info
Introduction -- . 1. Deep in the Anthropocene -- Perils and prospects -- Nuclear threats -- Eco-threats and tipping points -- Staying within planetary boundaries -- Climate change -- Clean-energy - and a 'Plan B'? -- 2. Humanity's future on Earth -- Biotech -- Cybertechnology, robotics, and AI -- What about our jobs? -- Human-level intelligence? -- Truly existential risks? -- 3. Humanity in a cosmic perspective -- The Earth in a cosmic context -- Beyond our solar system -- Spaceflight - Manned and unmanned -- Towards a post-human era? -- Alien intelligence? -- 4. The limits and future of science -- From the simple to the complex -- Making sense of our complex world -- How far does physical reality extend? -- Will science 'hit the buffers'? -- What about God? -- 5. Conclusions -- Doing science -- Science in society -- Shared hopes and fears.
Includes bibliographical references (pages [229]-235) and index.
Keywords: Technology -- Social aspects; Science -- Social aspects; Social prediction; Twenty-first century -- Forecasts; Future, The; Nonfiction; Forecasts; Creative nonfiction; Creative nonfiction